Etik, Dönüşümcü, Paternalist, Spiritüel ve Öğretimsel Liderlik Stillerinin Karşılaştırılması - Özgenel, Mustafa; Yıldız, Baran Barış; Mert, Pınar; Dursun, İsmail Eray (Fırat University, 2021)
Bu araştırmada okul müdürlerinin etik, dönüşümcü, babacan/paternalist, ruhsal/spiritüel ve öğretimsel liderlik stillerinin karşılaştırılması amaçlanmıştır. Bu amaç doğrultusunda araştırma betimsel tarama desenine göre gerçekleştirilmiştir. Araştırmaya İstanbul ilinden 586 öğretmen katılmıştır. Okul müdürlerinin öğretmenler tarafından algılanan liderlik stilleri arasında pozitif yönde yüksek düzeyde anlamlı ilişki tespit edilirken; öğretmenler okul müdürlerinin en fazla etik liderlik stilini en az ise paternalist liderlik stilini sergilediğini düşünmektedir. Öğretmenlerin öğretimsel, dönüşümcü, etik ve ruhsal liderlik stilleri algıları cinsiyetlerine göre anlam farklılık gösterirken; eğitim durumlarına göre anlamlı farklılık göstermemektedir. Öğretmenlerin görev yaptıkları okul/kurum türüne/kademesine ve yaşlarına göre okul müdürlerinin öğretimsel, dönüşümcü, etik, paternalist ve ruhsal liderlik stilleri anlamlı farklılık gösterdiği tespit edilmiştir. Okul müdürlerinin öğretimsel, dönüşümcü, paternalist ve ruhsal liderlik stilleri öğretmenlerin kıdemlerine göre anlamlı farklılık göstermediği; ancak okul müdürlerinin etik liderlik stili öğretmenlerin kıdemlerine göre anlamlı farklılık gösterdiği belirlenmiştir.

In this study, it is aimed to compare the ethical, transformational, paternalistic, spiritual, and instructional leadership styles of school principals. For this purpose, the research has been carried out according to the survey model. 586 teachers from Istanbul province participated in the study. A high level of a positive correlation has been found between the leadership styles of school administrators perceived by the teachers. Teachers most perceived ethical leadership style and least perceived paternalist leadership style of school administrators. While teachers' perceptions of instructional, transformational, ethical, and spiritual leadership styles differ significantly according to their gender; It does not differ significantly according to their educational status. It has been determined that the instructional, transformational, ethical, paternalist, and spiritual leadership styles of school administrators differ significantly according to the type, grade, and age variables. The instructional, transformational, paternalist and spiritual leadership styles of school principals do not differ significantly according to the seniority variable; however, it has been determined that the ethical leadership style of school administrators differed significantly according to the seniority variable. It has been determined that instructional, transformational, ethical, paternalist, and spiritual leadership styles of school administrators differ significantly; according to the type of schools, grade, and age variables.
COMPARISON OF ETHICAL, TRANSFORMATIONAL, PATERNALISTIC, SPIRITUAL AND INSTRUCTIONAL LEADERSHIP STYLES